Becoming Zimbabwe. A History from the Pre-colonial Period to 2008 : A History from the Pre-colonial Period to 2008 - Raftopoulos, Brian (Book collections on Project MUSE., 2009)
Becoming Zimbabwe is the first comprehensive history of Zimbabwe, spanning the years from 850 to 2008. In 1997, the then Secretary General of the Zimbabwe Congress of Trade Unions, Morgan Tsvangirai, expressed the need for a 'more open and critical process of writing history in Zimbabwe. ... The history of a nation-in-the-making should not be reduced to a selective heroic tradition, but should be a tolerant and continuing process of questioning and re-examination.' Becoming Zimbabwe tracks the idea of national belonging and citizenship and explores the nature of state rule, the changing contour.